2013
DOI: 10.1002/lt.23682
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in liver transplant recipients in the model for end-stage liver disease era: An analysis of the epidemiology, risk factors, and outcomes

Abstract: In recipients of liver transplantation (LT), surgical site infection (SSIs) are among the most common types of infection occurring in the first 60 days after LT. In 2007, the Model for End-Stage Liver Disease (MELD) scoring system was adopted as the basis for prioritizing organ allocation. Patients with higher MELD scores are at higher risk for developing SSIs as well as other health care-associated infections. However, there have been no studies comparing the incidence of SSIs in the pre-MELD era with the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
35
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 39 publications
11
35
3
2
Order By: Relevance
“…Other authors have shown that CRAB is the MDR-GNB that most often colonizes LT recipients before and after transplant. (14,15) Although the prevalence of CRAB colonization was quite high in our patient sample, there are, to our knowledge, no comparative data in the literature regarding the prevalence of CRAB colonization in the context of active, weekly surveillance after LT.…”
Section: Discussionmentioning
confidence: 80%
“…Other authors have shown that CRAB is the MDR-GNB that most often colonizes LT recipients before and after transplant. (14,15) Although the prevalence of CRAB colonization was quite high in our patient sample, there are, to our knowledge, no comparative data in the literature regarding the prevalence of CRAB colonization in the context of active, weekly surveillance after LT.…”
Section: Discussionmentioning
confidence: 80%
“…Cold ischemia time longer than 400 minutes has previously been identified as a risk factor for SSI after LT, (32) and in the present study a prolonged total ischemia time was associated with an increased risk for infection by CRPA. In general, it can be assumed that longer ischemia time is associated with slower post-LT recovery of the systemic inflammatory response, as well as, indirectly, longer ICU stays, increased use of invasive devices, and delayed recovery of renal function.…”
Section: Discussionsupporting
confidence: 59%
“…Other authors have shown that CRAB is the MDR GNB that most often colonizes LT recipients before and after transplant. (32) Although the prevalence of CRAB colonization was quite high in our patient sample, there are, to our knowledge, no comparative data in literature regarding the prevalence of CRAB colonization in the context of active, weekly surveillance after LT.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations